1984
DOI: 10.4141/cjps84-073
|View full text |Cite
|
Sign up to set email alerts
|

A Growth Chamber Study of Copper Nutrition of Cereal and Oilseed Crops in Organic Soil

Abstract: Copper nutrition of barley (Hordeum vulgare'Conquest'), oats (Avena sativa 'Hudson'), wheat (Triticum aestivum 'Neepawa'), flax (Linum usitatissium 'Dufferin') and canola (Brassica campestis 'Torch') was studied on a severely Cu-deficient organic soil in a controlled environment growth chamber. The objective of the study was to facilitate identification of Cu-related growth disorders by establishing the critical levels for Cu in plant tissues of the crops listed above.Copper deficiency symptoms were exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Yield response of cereals due to Cu fertilization has also been investigated in Western Canada Kruger et al, 1985;McAndrew et al, 1984). However, little information is available on the effect of different methods, sources and rates of Cu application in correcting Cu deficiencies for Western Canadian soils (Karamanos et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Yield response of cereals due to Cu fertilization has also been investigated in Western Canada Kruger et al, 1985;McAndrew et al, 1984). However, little information is available on the effect of different methods, sources and rates of Cu application in correcting Cu deficiencies for Western Canadian soils (Karamanos et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Smilde and Henkens (1967) reported that sensitivity to copper deficiency was generally greatest in wheat, lowest in oats and intermediate in barley. A further study by McAndrew et al (1984), also demonstrated that wheat was the most sensitive cereal to copper deficiency, followed by oats and barley. Nambiar (1976) showed that cultivars of a cereal may vary in their sensitivity to low soil copper levels but the yields of some oat cultivars were more affected by the copper deficiency than those of wheat cultivars, The objective of the present study was to compare stem melanosis, yield, height, thousand kernel weight (TKW), and vigour of various wheat (Triticum aestivum L.), barley (Hordeum vulgare L.), and oat (Avena saliva L.) cultivars grown on a copper deficient soil with or without added copper.…”
mentioning
confidence: 88%